Analysis Of Digital Transformation In Improving Msme Performance And Public Services In Indonesia - Rahmat Al Hidayat; Rahmat Fathoni; Herimanto Herimanto (International Journal of Social and Management Studies, 2026)
Digital transformation has become a strategic necessity in driving economic growth and improving the quality of public services in Indonesia. This study aims to analyze the role of digital transformation in enhancing the performance of Micro, Small, and Medium Enterprises (MSMEs) and public service delivery, as well as to identify the challenges and optimization strategies involved. The research employs a qualitative approach using a literature review method, drawing data from relevant scientific journals, government reports, and academic publications. The findings reveal that digital transformation significantly improves MSME performance through increased operational efficiency, expanded market access, enhanced competitiveness, and product innovation. In the public sector, digitalization contributes to more efficient, transparent, and accessible services, thereby improving government accountability and responsiveness. However, the implementation of digital transformation still faces several challenges, including uneven digital infrastructure, low digital literacy among human resources, limited technological access, and increasing cybersecurity risks. These obstacles create a gap between the potential benefits of digital transformation and its actual implementation. Therefore, a comprehensive strategy is required to optimize digital transformation, including improving digital literacy, strengthening digital infrastructure, reforming adaptive policies, and enhancing collaboration among stakeholders such as government, private sector, academia, and society. This study concludes that digital transformation not only serves as a technological innovation but also as a key driver for sustainable economic development and improved governance. The findings are expected to provide insights and recommendations for policymakers in formulating effective strategies to accelerate inclusive and sustainable digital transformation in Indonesia.